Indigenous knowledge driven nature-based solutions: findings from an international design competition - Maibritt Pedersen Zari; Mercia Abbott; India Chenery; Huhana Smith; Rebecca Kiddle; Lama Tone; Selina Ershadi (Nature-Based Solutions)
Nature-based solutions (NbS) strengthen biodiversity and ecosystems but should also centre human wellbeing. Understandings of wellbeing differ however and relate closely to cultural values, relationships with nature, and worldviews. This means that NbS can hold very different meanings across contexts, reflecting varying cultural values and understandings of wellbeing. This is true in the culturally diverse region of Te Moananui Oceania (the island nations of the Pacific), where relationships to nature and cultural worldviews are unique. The region is where many nations most impacted by climate change are located. NbS offer significant potential for effective climate change adaptation and are increasingly being explored and utilized in Te Moananui Oceania.To explore nature-based adaptation agendas grounded in Indigenous ecological knowledge and cultural understandings of wellbeing, and to strengthen connections between NbS and place-based worldviews in urban climate adaptation, an international design competition focused on urban NbS in Te Moananui Oceania was held in 2023. This design-led research methodology was used to both understand how people were already thinking about and implementing NbS in relation to the range of Indigenous knowledge in the region as a means to adapt to climate change. The competition was also a means to capture and exhibit the collective imagination regarding climate futures in an inclusive, enabling, and impactful way. Strategies offered by competition entrants in turn informed ongoing research into how to design effective NbS in the region. We examine the usefulness of the design competition as a research methodology, and its suitability to bridge cultural differences, political agendas, and varying worldviews in the climate change adaptation arena.Findings from over 70 entries revealed that working with water-based ecologies, storytelling, and relational place-based design were recurring themes. Many projects combined Indigenous and contemporary knowledge systems, suggesting that hybrid approaches have value. We argue that design competitions can be effective research tools; supporting dialogue across worldviews and illustrating contextually grounded strategies for just climate adaptation. For climate adaptation to be realistic, effective, culturally relevant, and just, a deep and considered understanding of connection to place and a place’s people is vital.